ece306-7

# ece306-7 - Recursive and Nonrecursive Discrete-Time Systems...

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Recursive and Nonrecursive Discrete-Time Systems If a system output y(n) at time n depends on any number of past output value y(n-1), y(n-2),... , it is called a recursive system. Let's have a DTS that gives the cumulative average y ( n) = 1 n x(k ) n + 1 k =0 n -1 k =0 We can find y(n) more efficient by utilizing the output y(n-1). y (n ) = = 1 n +1 x(k ) + x(n ) 1 ( ny (n - 1) + x(n ) ) n +1 n 1 = y ( n - 1) + x(n ) n +1 n +1 1 Recursive and Nonrecursive Discrete-Time Systems x(n) + X y(n) 1 n+1 X z-1 n This system requires two multiplication, one addition, and one memory location. This is a recursive system which means the output at time n depends on any number of a past output values. So, a recursive system has feed back output of the system into the input. This feed back loop contains a delay element. y (0) = x (0) y (1) = 1 1 y (0) + x(1) 2 2 y (2) = y ( n0 ) = 2 1 y (1) + x(2) 3 3 n0 1 y ( n0 - 1) + x( n0 ) n0 + 1 n0 + 1 Recursive and Nonrecursive Discrete-Time Systems For the causal FIR systems y ( n) = M k =0 h( k ) x ( n - k ) = F [ x(n), x(n - 1),..., x( n - M ) ] = h(0) x(n) + h(1) x(n - 1) + ... + h( M ) x(n - M ) x(n) F[x(n),x(n-1), ...,x(n-M)] y(n) x(n) F[y(n-1),..y(n-N), x(n),...,x(n-M)] z-1 y(n) Nonrecursive system Recursive system 2 ! " \$ # ' % ( & & & Let's have a recursive system that is first-order difference X(n) y(n) + a y ( n) = ay ( n - 1) + x ( n) z-1 where is a constant and system is time invariant. We assume that we have initial condition y(-1). For , y(n) can be obtained y (0) = ay (-1) + x(0) y (1) = ay (0) + x (1) = a 2 y (-1) + ax (0) + x(1) n k =0 y (n) = a n+1 y ( -1) + a n x(0) + a n-1 x(1) + ... + x( n) y (n) = a n+1 y (-1) + a k x(n - k ) n0 ! ! The response y(n) of the system depends on initial condition y(-1) of the system and the system response to the input signal If the system is initially relaxed at time n=0, its memory should be zero. So, y(-1)=0. Then, system is at zero state and the corresponding output is called zero-state response or forced response. y zs (n) = n k =0 a k x(n - k ) n0 If system is initially nonrelaxed (y(-1)0) and the input x(n)=0 for all n. The corresponding output is called zero-input response or natural response. y zi (n) = a n+1 y (-1) n0 3 ! The total system response is y (n) = yzs (n) + y zi (n) General form of linear constant-coefficient difference equation is y ( n) = - N k =0 N k =1 M k =0 ak y ( n - k ) + M k =0 bk x (n - k ) ak y ( n - k ) = bk x (n - k ) In order to find y(n), we need to know initial conditions y(n-1), y(-2),...,y(n-N) and the input x(n) for all n>=0. Recursive system may be relaxed or non-relaxed, depending on the initial condition. ! A system is linear if satisfy the following requirements: 1. The total response is equal to the sum of the zero-input and zero-state responses y (n) = y zs (n) + yzi (n) 2. The principles of superposition applies to the zero-state response (zero-state linear) 3. The principles of superposition applies to the zero-input response (zero-input linear) If a system does not satisfy all three separate requirement, system is called nonlinear. ) 4 ...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online